PELAKSANAAN PERSYARATAN TEKNIS DEPOT AIR DALAM UPAYA MEMBERIKAN PERLINDUNGAN KEPADA KONSUMEN DI KOTA PONTIANAK - NIM. A1011201065, FITRIANI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract In order to guarantee the quality of drinking water products produced by refill drinking water depots that meet drinking water quality requirements, it is necessary to have provisions governing the existence of refill drinking water depots in an effort to provide protection to consumers of these water depots. In this research the author uses empirical research methods and is descriptive in nature, the aim of this research is to obtain data and information on water depots, factors that refill water depot entrepreneurs have not implemented the provisions as intended in Article 7 paragraph (2) paragraph (2), legal consequences for entrepreneurs who do not implement the provisions of Article 7 paragraph (2) paragraph (2), as well as the role of the Pontianak City Department of Industry, Trade, Energy and Mineral Resources in supervising or preventing business actors from not implementing Article 7 paragraph (2) Decree of the Minister of Industry and Trade Number 651/Mpp/Kep/10/2004 Concerning Technical Requirements for Drinking Water Depots and Trade. The results of this research show that water depot entrepreneurs in Pontianak City have not carried out their obligations regarding Article 7 paragraph (2) of Decree of the Minister of Industry and Trade Number 651/Mpp/Kep/10/2004 concerning Technical Requirements for Drinking Water Depots and Trade. The factor that causes Water Depot entrepreneurs not to comply with Article 7 paragraph (2) is that they do not understand the regulations, namely in accordance with Article 7 paragraph (2) paragraph (2). The legal consequences for water depot entrepreneurs who do not comply with the provisions of Article 7 paragraph (2) are taking administrative action against water depot entrepreneurs, namely verbal warnings, written warnings, temporary suspension of business activities, and revocation of business permits. The efforts of the Department of Industry, Trade, Energy and Mineral Resources of Pontianak City to supervise or prevent water depot business actors who do not implement Article 7 paragraph (2) are to carry out regular and continuous education and supervision, especially regarding Article 7 paragraph (2) Decree Minister of Industry and Trade Number 651/MPP/Kep/10/2004 concerning Technical Requirements for Drinking Water Depots and Trade, which aims to protect the public from disease or health problems. Keywords: Stock, Gallons, Depot and Water Abstrak Dalam rangka menjamin mutu produk air minum yang dihasilkan oleh depot air minum isi ulang yang memenuhi persyaratan kualitas air minum, perlu adanya ketentuan yang mengatur keberadaan depot air minum isi ulang dalam upaya memberi perlindungan kepada konsumen depot air tersebut. Dalam Penelitian ini Penulis menggunakan metode penelitian empiris dan bersifat deskriptif, tujuan penelitin ini adalah untuk memperoleh data dan informasi depot air , faktor pengusaha depot air isi ulang belum melaksanakan ketentuan sebagaimana yang dimaksud dalam Pasal 7 ayat (2) ayat (2), akibat hukum bagi pengusaha yang tidak melaksanakan ketentuan Pasal 7 ayat (2) ayat (2), serta peran Dinas Perindustrian, Perdagangan, Energi dan Sumber Daya Mineral Kota Pontianak dalam mengawasi atau mencegah terhadap pelaku usaha tidak melaksanakan Pasal 7 ayat (2)Keputusan Menteri Perindustrian Dan Perdagangan Nomor 651/Mpp/Kep/10/2004 Tentang Persyaratan Teknis Depot Air Minum Dan Perdagangannya. Hasil penelitian ini, pihak pengusaha depot air Di Kota Pontianak belum melakukan kewajibannya terhadap Pasal 7 ayat (2)Keputusan Menteri Perindustrian Dan Perdagangan Nomor 651/Mpp/Kep/10/2004 Tentang Persyaratan Teknis Depot Air Minum Dan Perdagangannya. Faktor yang penyebab pengusaha Depot Air tidak sesuai dengan Pasal 7 ayat (2)adalah adalah belum memahami terhadap peraturan yaitu sesuai dengan Pasal 7 ayat (2) ayat (2). Akibat Hukum Bagi Pengusaha Depot Air yang tidak sesuai dengan Ketentuan Pasal 7 ayat (2) adalah melakukan tindakan administratif bagi pengusaha depot air yaitu Teguran lisan, Teguran tertulis, Penghentian sementara kegiatan usaha, dan Pencabutan izin usaha. Upaya Dinas Perindustrian, Perdagangan, Energi dan Sumber Daya Mineral Kota Pontianak dalam mengawasi atau mencegah terhadap pelaku usaha depot air yang tidak melaksanakan Pasal 7 ayat (2) adalah melakukan edukasi dan pengawasan secara berkala dan berkesinambungan, khususnya terhadap Pasal 7 ayat (2)Keputusan Menteri Perindustrian dan Perdagangan Nomor 651/MPP/Kep/10/2004 tentang Persyaratan Teknis Depot Air Minum Dan Perdagangannya, yang bertujuan untuk melindungi masyarakat dari penyakit atau gangguan kesehatan.Kata Kunci : Stok, Galon, Depot dan Air